Effects of satellite lines in fittings of He-like triplets of X-ray Spectra. Issue Volume 15:Issue S350(2019) (April 2019) - Zhang, Lan; Xue, Xiangxiang; Yuan, Dawei; Wei, Huigang; Wang, Feilu; Zhao, Gang
Abstract: We estimate the wind speeds with a Bayesian inference and a Markov Chain Monte Carlo (MCMC) tool for the high resolution X-ray spectra of Vela X-1, to understand the effect of satellite lines on spectral analysis. After modelling continua and He-like triplets of the spectra with a parameterized two-component power-law model and a mullti-Gaussian model, respectively, we estimate the contamination from satellite lines, and improve the self-consistency of wind speeds derived from the He-like triplet lines of different elements. Moreover, our fitting shows that the column density of scatter component varies from phase to phase.